Two-step feeding pyro-gasification of coconut husk: effects of Ni-Fe impregnation on products yields and quality - Kumar R.; Mondal M.K. (My University, 2025)
Coconut husk is a promising biomass for renewable energy applications due to its abundance and high calorific value. However, enhancing its gasification performance requires innovative treatments and optimization. In this study, native green coconut husk (NGCH) was treated with electroplating industry wastewater and synthetic Ni-Fe solutions to impregnate metal constituents, aiming to improve fuel gas generation via CO2 pyro-gasification. This work compares NGCH, metal-impregnated NGCH from synthetic water (MICHs), and metal-impregnated NGCH from wastewater (MICHw) in an updraft fixed-bed gasification column. Experiments investigated the effects of temperature, CO2 flow rate, reaction time, and particle size on fuel gas composition, gross calorific value (GCV), and gasifier performance. Further tests varied impregnation temperatures under optimal conditions to study their impact on calorific value and gas yield. The GCV of untreated coconut husk (C48.74H88.33O36.91N, by ultimate analysis) was 15.46 MJ/kg. Ni and Fe concentrations in the wastewater were 280 mg/L and 5.01 mg/L, respectively, with a pH of 6.56. Scanning electron microscopy with energy-dispersive X-ray spectroscopy (SEM-EDX) quantified the structural differences among NGCH, MICHs, and MICHw. Fuel oil was generated from each biomass sample using a two-step feeding method: heating with N2 up to 700 °C, followed by CO2 gasification up to 850 °C. The oil was characterized using Fourier transform infrared spectroscopy (FTIR), 1H and 13C nuclear magnetic resonance (NMR), and high-resolution mass spectrometry (HRMS). Gasification efficiencies increased from 63 % to 79 % for NGCH, 71 %–81 % for MICHs, and 74 %–85 % for MICHw. MICHw demonstrated the highest GCV (22.97 MJ/Nm3) for fuel gas due to elevated CO and H2 concentrations at optimized conditions and a 105 °C impregnation temperature. These findings highlight the potential of metal-impregnated coconut husk for enhanced fuel gas production, providing a sustainable approach to biomass utilization and renewable energy generation. © 2025 Elsevier Ltd